Role of Community Medicine during COVID-19 Pandemic - Rao, Epari Venkata; Panda, Prem Sagar (Indian Journal of Community Health, 2021)
Pandemics have significantly affected economy of each country. Health & political system have been also drastically affected in each part of the country. To fight against pandemic, it demands multidimensional approaches comprising of various measures like surveillance, containment, isolation & quarantine, border restriction as well as various socio-political and community measures. Though the entire health workforce is involved at multiple levels, the role of a community medicine/public health expert is maximum in controlling the spread in the community and managing the situation. The community medicine specialists can contribute to the public health as well as health-care services in combating the pandemic. This review has been done for giving an insight of proper utilisation of public health services and existing manpower of community medicine. Also this will channelize our health system and give a direction for combating future public health crisis. So Government should utilise the experiences and expertise to manage the pandemic very well.